The impact of workplace bullying on project success as mediated through individual organizational citizenship behavior: a study in Pakistan - Fozia Mubarak; Sana Mumtaz (Cogent Business & Management, 2018)
This study examines the relationship between workplace bullying and project success in project based organizations in Pakistan. Additionally, this relationship was studied through the mediating effect of organizational citizenship behavior—individual (OCBI). Using a quantitative research method, data were collected from a number of project-based organizations in Pakistan. Based on the data collected from 254 respondents from different nongovernment organizations of Islamabad and Rawalpindi, findings suggest that project success is significantly associated with workplace bullying and OCBI. In addition, it was also revealed that employees who face more bullying at workplace have low level of OCBI at work. The study contributes to the current literature in organizational behavior and project management by exhibiting how that workplace bullying relates to project success, through mediating effect of OCBI.
Keywords: 650